Social class, sense of control, and social explanation - Kraus, Michael W; Piff, Paul K; Keltner, Dacher (Journal of personality and social psychology, 2009)
Lower social class is associated with diminished resources and perceived subordinate rank. On the basis of this analysis, the authors predicted that social class would be closely associated with a reduced sense of personal control and that this association would explain why lower class individuals favor contextual over dispositional explanations of social events. Across 4 studies, lower social class individuals, as measured by subjective socioeconomic status (SES), endorsed contextual explanations of economic trends, broad social outcomes, and emotion. Across studies, the sense of control mediated the relation between subjective SES and contextual explanations, and this association was independent of objective SES, ethnicity, political ideology, and self-serving biases. Finally, experimentally inducing a higher sense of control attenuated the tendency for lower subjective SES individuals to make more contextual explanations (Study 4). Implications for future research on social class as well as theoretical distinctions between objective SES and subjective SES are discussed.